EMERGENCE OF PUBLIC HEALTH CRISIS IN INDIA AMIDST COVID-19 - Madhuri Prakash Kubal; Archana Raman Belge (International Journal of Ayurveda and Pharma Research, 2021)
The Coronavirus Disease 2019 (COVID-19) has affected largest population of world in several aspects. The consequences of this pandemic are multidimensional. Developing countries like India, where health care system is already struggling with many problems, and sudden outburst of COVID-19 created major challenges in terms of public health management. During management of COVID-19 patients, in second most populous country of world, Indian health care system is overburdened. This has left impact on overall health care management of COVID-19 and non COVID-19 patients. Objective: To review the public health crisis created during COVID-19 in India. Method: Various articles and studies performed during COVID-19 related to health care management are referred to have critical review of COVID-19 situation, its management and public health care challenges. Result: In the process of containing COVID-19 spread and treatment various measures and guidelines has been adopted regarding health care like restrictions on hospitalization of other than COVID-19 patients, curtailing surgeries etc. Diversion of health care system to COVID-19 patients has affected essential health services like Immunization, ANC services, treatment for Non-communicable diseases. Conclusion: Preparation of health care system for future pandemic like conditions by instituting a regular audit at health care centres and hospitals has become necessary. Need of investing in infrastructure, effective planning and overall strengthening of primary health care services has been identified. It is foremost step to ensure their functioning during emergencies without affecting regular basic health services, which majorly contributes in population health.